Perencanaan Akibat Gempa Pada Bangunan Cagar Budaya, Istana Mini Banda, Kawasan Pulau Banda Neira - Rumihin, Angel; Rumihin, Ony Frengky (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2025)
The Mini Palace of Banda is a cultural heritage building located on Banda Neira Island, Central Maluku Regency, Maluku Province. Several earthquakes, including the significant event on January 10, 2023, have severely impacted historical structures in the region, including the Mini Palace. This study aims to develop a restoration plan for earthquake-induced damages while adhering to cultural heritage conservation principles. The research methods include an analysis of the existing building conditions, structural evaluations, and cost estimation for rehabilitation efforts. The findings indicate damage to the main Mini Palace building, the residence building, auxiliary buildings, and the exile house of Bung Hatta. Structural evaluations highlight the need for repairs to the roofing, walls, and reinforcement of the foundations to ensure the stability of the structures. Rehabilitation cost estimations reveal allocation proportions of 20.10% for the Mini Palace, 8.254% for the residence building, and 16.95% for the auxiliary buildings from the total budget of IDR 15,660,455,000.00. This study contributes by providing a technical planning framework for the post-earthquake rehabilitation of cultural heritage buildings while preserving their historical, architectural, and cultural values.